Physicochemical Processes Occurring in the Activation of Gileads and Their Inclusion Into Vegetable Oils - Norkulov D., Sayimova D.K., Sultanov Sh.A. (American Journal of Biodiversity, 2024)
The nature of the interaction of sorption properties of vegetable oils introduced for sorption purification of raw materials from impurities in the production of environmentally friendly food products and biologically active media is shown. Sorbents, in particular palygorskite clays, are used to purify vegetable oils from additives that complicate the processing of these raw materials into products with high energy and nutritional value. The introduction of palygorskite clays into vegetable oils through chemical processes seems to be a reasonable step, since on their surface (i.e., the basal surfaces and edges of the particles) there are both acidic and basic surface centers. By further separating such clays from the liquid phase, it is possible to obtain a very wide range of compounds of various nature, which are to some extent close to the main component of the oil-containing medium - triglycerides of fatty acids. So, for example, free fatty acids are characterized by the presence of a proton of the hydroxyl group and a coordination saturated carbonyl oxygen atom; the active part of peroxide compounds contains an electron donor oxygen atom, and the molecules of mixed phosphatides have donor-acceptor bonds at the oxygen atom and the amino group.